PENGARUH KUALITAS PELAYANAN TAKSI ONLINE “MY BLUEBIRD’ DAN “GRAB” TERHADAP CITRA PERUSAHAAN - Susan Sri Apriyani; Marwan Mahmudi (Universitas Mercu Buana, 2020)
Bluebird and Grab are two professional transportation service companies in Indonesia. The two have been competiting to serve their best to satisfy the customers so the positive image will stay remain. The concept of this research is using theory quoted from Kotler of serving quality and company image by Shirley Harrison. Method used quantitative approach in possitivm paradigma and comparative study. The survey method is using questionaire and the score of the result has been measured using Likert scale.. The questionaire has been sproud to 77 of Mercu Buana University students of Communication, major of Public Relations in 2015 to 2017 that has been a user of Bluebird Taxi and Grab Car. The data has been processed using SPSS 20 in Person’s correlation, simple linear regretion test, and paired sample t-test. There, we found the strong connection of Taksi Bluebird service quality to the company image for 0.792 and also of the Grabcar for 0.62. It proves the impact of service quality to the company image. The difference is that the contribution of service quality to Bluebird Taxi company is 62.7% and to Grabcar company is 39.4%. It’s because Bluebird Taxi focuses more to the transportation service